-35x+42=-29x-6

Simple and best practice solution for -35x+42=-29x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -35x+42=-29x-6 equation:


Simplifying
-35x + 42 = -29x + -6

Reorder the terms:
42 + -35x = -29x + -6

Reorder the terms:
42 + -35x = -6 + -29x

Solving
42 + -35x = -6 + -29x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '29x' to each side of the equation.
42 + -35x + 29x = -6 + -29x + 29x

Combine like terms: -35x + 29x = -6x
42 + -6x = -6 + -29x + 29x

Combine like terms: -29x + 29x = 0
42 + -6x = -6 + 0
42 + -6x = -6

Add '-42' to each side of the equation.
42 + -42 + -6x = -6 + -42

Combine like terms: 42 + -42 = 0
0 + -6x = -6 + -42
-6x = -6 + -42

Combine like terms: -6 + -42 = -48
-6x = -48

Divide each side by '-6'.
x = 8

Simplifying
x = 8

See similar equations:

| 0=4x^2+12x+13 | | -8+4x=2x+18 | | -2(2x-9)-7x=30 | | 2(20y-20)=-5(20-12y) | | -5(x-4)-25=-5 | | -4x-4=-2x+12 | | 3p-15+3p=-27 | | 7X+10y=655 | | 900x+45= | | 8x-18=6x+2 | | 9=12t | | 110+t^2=190+2t | | -6+2x=8+3x | | -7(5n-16)=-7n | | t+75=4t | | b+9=4b | | -11+5x=4+6x | | 2(4x-3)-8=4(4-2x) | | s+81=2s | | -20h=-7(4h+20)-12 | | 90-2x=-5+3x | | x-40=-5x+50 | | -2.25(x-1.5)(x-6)=0 | | b+28=5b | | c+13=2c | | -x+0.25y-s=-1.75 | | -3x-14=-6x+25 | | 17.5g+8.29=-2(-11.1g-18.48) | | -16+36=-4(x+9) | | (X-4)(x-4)=44 | | 8x-11=5x+11 | | 6(2n+3)=8(5n+2)+3 |

Equations solver categories